A taxonomy of vocabulary learning strategies used in massively multiplayer online role-playing games. (26th May 2015) - Bytheway, Julie
Abstract : Initiated in response to informal reports of vocabulary gains from gamers at universities in New Zealand and the Netherlands, this qualitative case study explored ways English language learners autonomously learn vocabulary while playing massively multiplayer online role-playing games (MMORPGs). Using research processes inherent in Grounded Theory, data was collected from a criterion sample of six English Second-Language (ESL) experienced players of World of Warcraft®. Data included semi-structured interviews, observations, elicited email texts and extant texts. Data was transcribed, coded, and refined through a cyclic process of constant comparative analysis until patterns emerged. The results revealed 15 vocabulary learning strategies, including noticing frequency, recognizing knowledge gap, selecting words for attention, equating images and actions to word, giving and receiving explanations and feedback, observing players, using words to learn words, reading in-game information, and using Google. Commercial off-the-shelf MMORPGs are valuable vocabulary learning contexts because meaningful communication is an inherent and enormous part of gameplay. In addition, hundreds of millions of ESL learners use digital games outside schools for informal language learning. This taxonomy of 15 vocabulary learning strategies provides a framework for further research into autonomous learning in informal digital contexts.